2011
DOI: 10.1111/j.1365-294x.2011.05313.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the landscape on boreal toad gene flow: does the pattern-process relationship hold true across distinct landscapes at the northern range margin?

Abstract: Understanding the impact of natural and anthropogenic landscape features on population connectivity is a major goal in evolutionary ecology and conservation. Discovery of dispersal barriers is important for predicting population responses to landscape and environmental changes, particularly for populations at geographic range margins. We used a landscape genetics approach to quantify the effects of landscape features on gene flow and connectivity of boreal toad (Bufo boreas) populations from two distinct lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…Most population genetic studies of amphibians assume individuals at a breeding pond represent a population (e.g., Tallmon et al 2000;Spear et al 2005;Moore et al 2011). However, these delineations may not represent genetic populations, leading to bias in subsequent analyses (e.g., Funk et al 2005;Giordano et al 2007).…”
Section: Genetic Analysesmentioning
confidence: 99%
“…Most population genetic studies of amphibians assume individuals at a breeding pond represent a population (e.g., Tallmon et al 2000;Spear et al 2005;Moore et al 2011). However, these delineations may not represent genetic populations, leading to bias in subsequent analyses (e.g., Funk et al 2005;Giordano et al 2007).…”
Section: Genetic Analysesmentioning
confidence: 99%
“…A key finding of several of the studies in Table 2 is the different patterns seen over diverse scales and sampling regimes. For instance, researchers have found differing effects of landscapes on amphibians by looking at different regions inhabited by a single species (Johansson et al 2005;Wang et al 2009aWang et al , 2011Moore et al 2011;Trumbo et al 2013), different species within the same region (Goldberg & Waits 2010;Richardson 2012), different time periods for the same metapopulation (Savage et al 2010) and different spatial scales for the same analysis (Angelone et al 2011). These results collectively challenge the generality of results that stem from landscape genetic studies, and suggest that results from molecular studies of amphibian-landscape interactions should generally be interpreted within the scope of a specific study or region, but not beyond.…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…14 microsats Landscape variables have drastically different effects on spotted salamanders than on wood frogs Moore et al (2011) Boreal toad (Bufo boreas) 11 microsats Saltwater and landscape cover influence gene flow for boreal toads in one region of southeast Alaska, but not in another Angelone et al (2011) European tree frog (Hyla arborea)…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…Several studies have compared results from LCPs and circuit-based estimates, leading to contrasting results. It was suggested that circuit-based estimates perform better than LCPs, except in cases where populations are narrowly distributed along linear bands of suitable habitat (Schwartz et al 2009, Moore et al 2011). In our study circuit-based estimates performed better, although the improvement was relatively low.…”
Section: Circuit-based Estimates Provide Limited Improvementsmentioning
confidence: 99%